Beauty as the Raiment of the Good. From Plotinus to Stróżewski and Tischner - Baranowska, Maria Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Relationship between goodness and beauty has been considered byphilosophers since ancient times. Plato identified them with one another. According to Plotinus and other Neoplatonists beauty has its origin in the good, reveals it, and directs us to it. The Middle Ages continued this tradition, reflected in the theory of the transcendentalsand in the understanding of beauty as harmony and radiance. In contemporary Polish philosophy, Platonic and especially Neoplatonic themes can be found in the thought of Władysław Stróżewski and Józef Tischner. They represent a common featureof the two conceptions, which otherwise differ in many respects. For Tischner beauty turns out to be not only an element, in which one can lose oneself, but also light and grace, a gift of the highest good. According to Stróżewski beauty, understood as radiance and perfection, comes as a gift from above, and inclines one to rise to what is highest (trans. Jarosław Olesiak).